Method for recovery of enteric viruses from estuarine sediments with chaotropic agents. - Wait, D A (1983)
An evaluation was made of the ability of chaotropes, low-molecular-weight ionic compounds which enhance the solubilization of hydrophobic compounds in water, to improve the recovery of enteric viruses from highly organic estuarine sediments. Chaotropic agents alone were poor eluents of polioviruses from sediment but were effective when combined with 3% beef extract. Chaotropes of lower potency, NaNO3, NaCl, and KCl, were more efficient eluents than the stronger chaotropes, guanidium hydrochloride or sodium trichloroacetate. The most effective eluent was 2 M NaNO3 in 3% beef extract at pH 5.5, which eluted 71% of sediment-associated polioviruses. Efficient concentration of the sodium nitrate-beef extract eluate by organic flocculation required the addition of the antichaotrope (NH4)2SO4 to a 2 M concentration and Cat-Floc T (Calgon, Pittsburgh, Pa.) a cationic polyelectrolyte, to a 0.01% concentration. Dialysis of the final concentrate was necessary to reduce salts to nontoxic levels before assay in cell cultures. Trials with highly organic estuarine sediment seeded with high or low numbers of poliovirus 1, echovirus 1, or rotavirus SA-11 demonstrated the superiority of this method over two other methods currently in use.